2021
DOI: 10.1039/d1ra06206a
|View full text |Cite
|
Sign up to set email alerts
|

Systematic laboratory approach to produce Mg-rich carbonates at low temperature

Abstract: Carbonates with a mol% of Mg above 40 were obtained exclusively in the presence of organic molecules. The mode used to add carbonate to the solution obtaining supersaturation has a significant impact on the forming mineral phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Dolomite was only observed in one of three lake sediments that were collected from a small depression on the edge of the lake that was likely isolated from the lake in the past, suggesting the dolomite has not precipitated from the present‐day lake. Dolomite is rare in alkaline lakes and playa containing hydromagnesite deposits (Chagas et al., 2016; Zeyen et al., 2021), and its precipitation is kinetically inhibited at Earth surface temperatures and pressures and may not even occur when supersaturated in solution (Al Disi et al., 2021). Although dolomite could explain the Mg isotope offset between the input water and the lake, it is not considered further in the model that is developed below since it is not thought to form from the modern lake water.…”
Section: Discussionmentioning
confidence: 99%
“…Dolomite was only observed in one of three lake sediments that were collected from a small depression on the edge of the lake that was likely isolated from the lake in the past, suggesting the dolomite has not precipitated from the present‐day lake. Dolomite is rare in alkaline lakes and playa containing hydromagnesite deposits (Chagas et al., 2016; Zeyen et al., 2021), and its precipitation is kinetically inhibited at Earth surface temperatures and pressures and may not even occur when supersaturated in solution (Al Disi et al., 2021). Although dolomite could explain the Mg isotope offset between the input water and the lake, it is not considered further in the model that is developed below since it is not thought to form from the modern lake water.…”
Section: Discussionmentioning
confidence: 99%
“…This formula has been debated for over 100 years since 1890, [15] and classified based on its carbonate group as either MgCO 3 • 3H 2 O [16][17][18][19] or Mg(HCO 3 )OH • 2H 2 O. [20][21][22] One set of studies has used infrared spectroscopy (IR), Raman spectroscopy, and thermogravimetric analysis (TGA) to characterize the materials, and these groups identified the presence of bicarbonate and hydroxyl groups. [20,21,23,24] Another complementary study by IR and Raman spectroscopies [25] and X-ray diffraction (XRD) [18,19] favored the (hydrated) carbonate form.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a dispute regarding the chemical formula of nesquehonite (or the disposition of water in the structure). This formula has been debated for over 100 years since 1890, [15] and classified based on its carbonate group as either MgCO 3 ⋅ 3H 2 O [16–19] or Mg(HCO 3 )OH ⋅ 2H 2 O [20–22] . One set of studies has used infrared spectroscopy (IR), Raman spectroscopy, and thermogravimetric analysis (TGA) to characterize the materials, and these groups identified the presence of bicarbonate and hydroxyl groups [20,21,23,24] .…”
Section: Introductionmentioning
confidence: 99%
“…First, there is a need to assess the taphonomic processes that affected these more or less ancient materials (De Boever et al, 2017). Additionally, the study of present-day analogs appears crucial to understand the relationships between the mineralogical and chemical composition of stromatolites, their micro-and macro-textures and the biological and environmental conditions prevailing where these microbialites form (Zeyen et al, 2021(Zeyen et al, , 2017 For example, several authors (Al Disi et al, 2021;Ries, 2010;Ries et al, 2008) proposed that the nature of the carbonate mineral phases composing modern stromatolites (e.g., Mg-calcite, aragonite and/or hydromagnesite) is primarily determined by the aqueous dissolved (Mg/Ca) ratio in the solution where they form. Lately, Zeyen et al (Zeyen et al, 2021) further suggested that water in which stromatolites form, may need to be saturated with an amorphous calcium carbonate (ACC) phase that would precipitate as a precursor phase before transforming to monohydrocalcite, Mg-calcite or aragonite depending on the (Mg/Ca)aq.…”
Section: Introductionmentioning
confidence: 99%
“…pH, temperature, Mg/Ca, salinity) on the precipitation of microbially mediatedMg-carbonates (Al Disi et al, 2019. For instance, in a sabkha environment, salinity, temperature, Mg/Ca (AlDisi et al, 2019) and carbonate supply(Al Disi et al, 2021) have a strong effect on bacterial activity, which in turn affect the incorporation of Mg within the calcite.…”
mentioning
confidence: 99%